PENGARUH BUDAYA ORGANISASI DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PT TECTRON MANUFACTURING - Angga Suswadi; Wasiman (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The purpose of this study is to examine and analyze the influence of organizational culture, work experience on employee productivity. This research was conducted in the city of Batam. The population in this study were employees found in PT Tectron Manufacturing Batam, with a population of 369 people. The sampling technique used in this study was purposive sampling method with a sample of 192 people. This study uses primary data and secondary data with data collection techniques using questionnaires, observations and data obtained from the company. Data were analyzed using validity test, reliability test, multiple regression analysis, F test, coefficient of determination test (R2), t test which was then processed using the SPSS 25 computer program. The results showed that organizational culture had a positive and significant effect on employee productivity, work experience positive and significant effect on employee productivity.